2016
DOI: 10.6060/mhc151205m
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Study of Nanostructured M-Monolayers and LS-Films of Triphenylcorrole

Abstract: An experimental and theoretical study of 5,10,15-triphenylcorrole (H 3 [(ms-Ph) 3 Cor]) nano-structured floating layers (M-layers) [(ms-Ph) 3 Cor] на твердых подложках и изучены их спек-тральные характеристики.Ключевые слова: Плавающие монослои, 2D наноструктуры, М-наноагрегаты, модель М-монослоя, ЛШ-пленки, коррол.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It was shown earlier that metal free 5,10,15-triphenylcorrole in floating at the air-water interface layers and in LS films forms stable nanostructures of different types. [53,[63][64]66] In this work, the structure and properties of floating layers of copper 5,10,15-triphenylcorrole at the air-water interface in a wide range of initial surface coverage degrees (c face /c edge from 4/2.5 % to 93/58 %, Figure 2) were studied.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown earlier that metal free 5,10,15-triphenylcorrole in floating at the air-water interface layers and in LS films forms stable nanostructures of different types. [53,[63][64]66] In this work, the structure and properties of floating layers of copper 5,10,15-triphenylcorrole at the air-water interface in a wide range of initial surface coverage degrees (c face /c edge from 4/2.5 % to 93/58 %, Figure 2) were studied.…”
Section: Resultsmentioning
confidence: 99%
“…Note, that constants characterizing monolayer at a lower compression speed (v=2.3 cm 2 •min -1 ) are: (n) max =45, (D aggr ) const =11 nm, (c i-aggr ) const =75 %. [45] Thus, as compression speed of the layer increases, the maximum number of molecules It is shown that an increase in the compression rate leads to a decrease in the area per molecule in the aggregate (Figures 3a, 4) and a shift of the boundaries between layers of different types towards a lower degree of surface coverage (Δc face =1.9 % for face-on monolayers, Δc face =15.1 % for edge-on monolayers and Δc face =43.2 % for bilayer). At a high compression speed less stable layers with more dense nanoaggregates are formed.…”
Section: Resultsmentioning
confidence: 99%
“…[36,44] It was also shown that corroles at the air-water interface form nanostructured floating mono-and multilayers. [45,46] The effect of the initial surface coverage on the structure of the floating layers of 5,10,15-triphenylcorrol (H 3 [(ms-Ph) 3 Cor]) [45,46] and effect of temperature of subphase on the layers of (7,13-dimethyl-2,3,8,12,17,18-hexamethylcorrolato)manganese(III) [48] was demonstrated. It was revealed that triphenylcorrole is able to form J-aggregates in thin films.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, nanostructures of numerous biomolecules having different properties from those of the parent molecules and with great potential for various applications have been reported. , Self-assembly is a key player in material nanoarchitectonics, the nanostructures formed in this way arising from molecules carrying side groups that promote the process. Supramolecular polymers have been created using diverse self-assembly strategies. , The formation of different kinds of molecular assemblies from precursor compounds at the water surface has been reported. , We previously demonstrated the possibility of supramolecular design at the air–water interface by controlling the self-assembly of tetrapyrrole compounds into 2D and 3D nanostructures. The concept of nanostructuring of organic compounds at the air–water interface and a model of a floating layer, the structural units of which can be both individual molecules (Langmuir’s approach, special case) and their major nanostructures (so-called M-nanostructures, general case), were presented. The formation of the porphyrin supermolecules from magnesium porphine, a functional element of chlorophyll, was reported …”
Section: Introductionmentioning
confidence: 99%